High-stability water-white tackifying resin and preparation method thereof

By adopting fully sealed operation and carefully designed raw material ratio and production process, the problems of water-white viscosity-enhancing resin in oxidation stability, color control, compatibility and complex preparation process are solved, and a water-white viscosity-enhancing resin with high stability, excellent color and high compatibility are achieved, improving its performance and application range.

CN119912622APending Publication Date: 2025-05-02KAIHUA CHENGXIN RESIN CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411828742.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The existing water-white viscosity-enhancing resins have defects in oxidation stability, color control, compatibility and complex preparation process, which limits its performance and application range.

Method used

The production method of fully sealed operation is adopted to carefully design the raw material ratio and production process, including the use of water-soluble monomers, hydrophobic modified monomers, functional monomers and catalysts, and the high-stability water-white viscosity-enhancing resin is prepared through free radical polymerization and post-treatment steps.

Benefits of technology

It significantly improves the thermal stability and oxidation safety of the resin, realizes the preparation of colorless or close to No. 0 resin, improves compatibility with the adhesive material, simplifies the production process, reduces energy consumption and costs, and improves product quality and application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005185032330000071
    Figure BDA0005185032330000071
Patent Text Reader

Abstract

The invention relates to the technical field of resin production, in particular to high-stability water-white tackifying resin and a preparation method thereof.The high-stability water-white tackifying resin is prepared from, by weight, 32.7%-58.1% of a monomer A, 1.4%-6.7% of a monomer B, 5.2%-20.5% of a monomer C, 12.4%-29.3% of a functional monomer D and 0.1%-1.3% of a catalyst E. The water-white tackifying resin with stable quality and excellent performance can be prepared by accurately controlling the raw material ratio and the production process, the thermal stability and oxidation safety of the resin are effectively improved through fully-closed operation, and meanwhile, the water-white tackifying resin with excellent color and close to the 0 # color is prepared by adopting the well-designed production process. The resin has good intermiscibility with various bonding materials, and the adhesive power and the stability of the product are remarkably improved. In addition, the optimized production process simplifies the production process, reduces the energy consumption and the cost, and further improves the market competitiveness of the product.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of resin production, in particular to a high-stability water-white tackifying resin and a preparation method thereof. Background Art

[0002] In the prior art, the preparation of water-white tackifying resins faces some significant defects. First, the traditional preparation methods often adopt open or semi-open operations, which makes the material easy to oxidize at high temperatures, thereby affecting the thermal stability and oxidation safety of the resin. This makes the prepared resin prone to performance degradation during long-term storage or use.

[0003] Secondly, the water-white tackifying resin prepared in the prior art has challenges in color control. Due to the limitations of raw materials and preparation processes, it is difficult to prepare a water-white tackifying resin that is colorless or close to color 0, which is limited in some application fields that have strict requirements on color.

[0004] In addition, the tackifying resin in the prior art is also insufficient in terms of compatibility with other adhesive materials. Due to the limitations of factors such as the chemical structure and intermolecular forces of the resin, the compatibility of the resin with certain adhesive materials is poor, which affects the adhesion and stability of the product.

[0005] Finally, the preparation process of existing technologies is often complicated, requiring multiple production links and high energy consumption, which not only increases production costs but also limits the improvement of production efficiency.

[0006] In summary, the prior art has defects in the preparation of water-white tackifying resins, such as poor oxidation stability, difficulty in color control, poor compatibility, and complex preparation process. These defects limit the performance and application scope of the water-white tackifying resins. Summary of the invention

[0007] The purpose of the present invention is to provide a high-stability water-white tackifying resin and a preparation method thereof, so as to solve the problems of poor oxidation stability, difficult color control, poor compatibility and complex preparation process in the preparation of the existing water-white tackifying resin mentioned in the above background technology.

[0008] To achieve the above object, the present invention provides the following technical solutions:

[0009] A high-stability water-white tackifying resin comprises the following raw materials in total percentage: 32.7-58.1% of monomer A, 1.4-6.7% of monomer B, 5.2-20.5% of monomer C, 12.4-29.3% of functional monomer D and 0.1-1.3% of catalyst E, wherein:

[0010] The monomer A is a water-soluble monomer comprising at least one polymerizable double bond;

[0011] The monomer B includes a cross-linking agent monomer having at least two polymerizable double bonds;

[0012] The monomer C comprises a modified monomer having a hydrophobic group;

[0013] The functional monomer D is a monomer containing hydroxyl and carboxyl polar groups.

[0014] Preferably, 0.01%-1.0% of chain transfer agent F and 0.1%-10% of functional filler G are also included.

[0015] Preferably, the chain transfer agent F is selected from one or more of dodecanethiol, mercaptoethanol or β-mercaptoethanol.

[0016] Preferably, the functional filler G is one or more of silicates, calcium carbonate or nano-titanium dioxide.

[0017] Preferably, the monomer A is selected from acrylic acid, methacrylic acid or acrylamide.

[0018] Preferably, the monomer B is ethylene glycol dimethacrylate or divinylbenzene.

[0019] Preferably, the monomer C is butyl methacrylate or octyl acrylate.

[0020] Preferably, the functional monomer D is hydroxyethyl acrylate or glycidyl methacrylate.

[0021] Preferably, the catalyst E is potassium persulfate or azobisisobutyronitrile.

[0022] On the other hand, the present invention also provides a method for preparing a high-stability water-white tackifying resin, which specifically comprises the following steps:

[0023] S10 weighing materials: weighing each raw material according to weight percentage;

[0024] S20 premixing: premixing the weighed monomer A, monomer B, monomer C, functional monomer D, chain transfer agent F and functional filler G uniformly;

[0025] S30 Adding catalyst: slowly adding catalyst E to the mixture under stirring;

[0026] S40 polymerization reaction: under nitrogen protection, heat to 60℃~90℃ to carry out free radical polymerization reaction, and the reaction time is controlled at 4~8 hours until the system viscosity reaches the predetermined value;

[0027] S50 post-treatment: After the reaction is completed, the temperature is lowered to room temperature, an appropriate amount of neutralizer is added to adjust the pH value to 7-9, and unreacted impurities are removed by filtration to obtain a high-stability water-white tackifying resin solution;

[0028] S60 Drying and curing: remove most of the water from the above solution by spray drying or reduced pressure evaporation to obtain solid resin powder.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] 1. Improve thermal stability and oxidation safety: Since the present invention adopts a fully enclosed production method, it can effectively reduce the oxidation chance of the material at high temperature. This production method significantly improves the thermal stability and oxidation safety of the water-white tackifying resin, thereby ensuring the stability and durability of the resin in long-term use or high-temperature environments.

[0031] 2. Improve color: Through a carefully designed production process, the present invention can prepare a water-white tackifying resin with a color close to color 0. This colorless or light-colored resin is not only beautiful, but also has a wider application prospect in some fields with strict requirements on color (such as high-end coatings, inks, etc.).

[0032] 3. Improve the compatibility with adhesive materials: The water-white tackifying resin prepared by the present invention has better compatibility with adhesive materials such as EVA, SIS, SBS, etc. This excellent compatibility helps to improve the adhesion and stability of the product, thereby improving the overall performance and service life of the product.

[0033] 4. Simplify the production process, reduce energy consumption and cost: The present invention reduces production links, reduces natural energy consumption and workload by optimizing the production process. This not only improves production efficiency, but also reduces production costs, making the product more competitive in the market.

[0034] 5. Improve product quality: By precisely controlling the raw material ratio and production process, the present invention can prepare a water-white tackifying resin with stable quality and excellent performance. This high-quality resin can meet various application requirements and provide users with a better use experience. DETAILED DESCRIPTION

[0035] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0036] Example 1

[0037] Raw material ratio

[0038] Monomer A (acrylic acid): 45%

[0039] Monomer B (ethylene glycol dimethacrylate): 3%

[0040] Monomer C (butyl methacrylate): 15%

[0041] Functional monomer D (hydroxyethyl acrylate): 25%

[0042] Catalyst E (potassium persulfate): 0.5%

[0043] Chain transfer agent F (dodecyl mercaptan): 0.5%

[0044] Functional filler G (silicate): 1%

[0045] Preparation steps

[0046] 1. Weigh the raw materials according to the above ratio.

[0047] 2. Mix monomers A, B, C, D, F and G in advance.

[0048] 3. Slowly add catalyst E while stirring.

[0049] 4. Under nitrogen protection, heat to 70°C and carry out free radical polymerization for 6 hours until the system viscosity reaches 2000mPa·s.

[0050] 5. Cool to room temperature, add an appropriate amount of neutralizer to adjust the pH value to 8, and filter to remove unreacted impurities.

[0051] 6. Remove most of the water by spray drying to obtain solid resin powder.

[0052] Example 2

[0053] Raw material ratio

[0054] Monomer A (methacrylic acid): 50%

[0055] Monomer B (divinylbenzene): 5%

[0056] Monomer C (octyl acrylate): 10%

[0057] Functional monomer D (glycidyl methacrylate): 20%

[0058] Catalyst E (azobisisobutyronitrile): 0.8%

[0059] Chain transfer agent F (mercaptoethanol): 0.7%

[0060] Functional filler G (calcium carbonate): 3%

[0061] Preparation steps

[0062] (Similar to Example 1, only the raw material ratio and the possible neutralizing agent to adjust the pH value are slightly different)

[0063] Example 3

[0064] Raw material ratio

[0065] Monomer A (acrylamide): 35%

[0066] Monomer B (ethylene glycol dimethacrylate): 2%

[0067] Monomer C (butyl methacrylate): 18%

[0068] Functional monomer D (hydroxyethyl acrylate): 30%

[0069] Catalyst E (potassium persulfate): 0.3%

[0070] Chain transfer agent F (β-mercaptoethanol): 0.5%

[0071] Functional filler G (nano titanium dioxide): 1.2%

[0072] Preparation steps

[0073] (Similar to Example 1, only the raw material ratio and the possible neutralizing agent to adjust the pH value are slightly different)

[0074] Comparative Example 1: High stability water-white tackifying resin without chain transfer agent and functional filler

[0075] Raw material ratio

[0076] This comparative example is intended to study the effects of chain transfer agent F and functional filler G on the performance of high stability water-white tackifying resin. Therefore, in terms of raw material ratio, except for not adding chain transfer agent F and functional filler G, the other raw materials and ratios are consistent with those in Example 1.

[0077] Monomer A (acrylic acid): 45%

[0078] Monomer B (ethylene glycol dimethacrylate): 3%

[0079] Monomer C (butyl methacrylate): 15%

[0080] Functional monomer D (hydroxyethyl acrylate): 25%

[0081] Catalyst E (potassium persulfate): 0.5%

[0082] Preparation steps

[0083] 1. Weigh the raw materials (excluding chain transfer agent F and functional filler G) according to the above ratio.

[0084] 2. Mix monomers A, B, C and D evenly in advance.

[0085] 3. Slowly add catalyst E while stirring.

[0086] 4. Under nitrogen protection, heat to 70°C and carry out free radical polymerization for 6 hours until the system viscosity reaches the predetermined value.

[0087] 5. Cool to room temperature, add an appropriate amount of neutralizer to adjust the pH value to 8, and filter to remove unreacted impurities.

[0088] 6. Remove most of the water by spray drying to obtain solid resin powder.

[0089] Expected Results

[0090] Due to the lack of chain transfer agent F, there may be a lack of effective chain length control during the polymerization reaction, resulting in a wide molecular weight distribution of the resin, thereby affecting its performance stability. In addition, due to the lack of functional filler G, some physical or chemical properties of the resin may not be effectively enhanced or improved.

[0091] Comparative Example 2: High stability water-white tackifying resin using non-water-soluble monomers

[0092] Raw material ratio

[0093] This comparative example aims to explore the effect of using a non-water-soluble monomer to replace the water-soluble monomer A on the performance of the high-stability water-white tackifying resin. Therefore, in terms of the raw material ratio, all monomer A is replaced with a non-water-soluble monomer (such as styrene), and the other raw materials and ratios are consistent with Example 1.

[0094] Monomer A (styrene): 45%

[0095] Monomer B (ethylene glycol dimethacrylate): 3%

[0096] Monomer C (butyl methacrylate): 15%

[0097] Functional monomer D (hydroxyethyl acrylate): 25%

[0098] Catalyst E (potassium persulfate): 0.5%

[0099] Chain transfer agent F (dodecyl mercaptan): 0.5%

[0100] Functional filler G (silicate): 1%

[0101] Preparation steps

[0102] 1. Weigh the raw materials according to the above ratio.

[0103] 2. Mix monomers A (styrene), B, C, D, F and G in advance.

[0104] 3. Slowly add catalyst E while stirring.

[0105] 4. Since monomer A is not water-soluble, it may be necessary to add an appropriate amount of emulsifier or dispersant during the polymerization process to form a stable emulsion or dispersion system.

[0106] 5. Under nitrogen protection, heat to 70°C and carry out free radical polymerization for 6 hours until the system viscosity reaches the predetermined value.

[0107] 6. Cool to room temperature, add an appropriate amount of neutralizer to adjust the pH to 8, and filter to remove unreacted impurities and emulsifier / dispersant.

[0108] 7. Remove most of the water by spray drying to obtain solid resin powder.

[0109] Expected Results

[0110] Since monomer A is non-water soluble, additional emulsifiers or dispersants may be required during the polymerization process to form a stable system, which may increase production costs and complexity. In addition, the use of non-water soluble monomers may affect the water solubility and water whiteness of the resin, thereby affecting its performance in certain applications. By comparing the results of Example 1 and Comparative Example 2, the effects of water soluble monomers and non-water soluble monomers on the properties of the resin can be evaluated.

[0111] The data of the high stability water-white tackifying resins prepared in the above three embodiments and the comparative example in terms of acid value, softening value, initial adhesion, lasting adhesion (70°C) and 180° peel strength at room temperature are compared, as shown in the following table:

[0112]

[0113] illustrate:

[0114] By analyzing the given table data, we can observe the following key points:

[0115] 1. Acid value (mg KOH / g)

[0116] The acid values ​​of Examples 1, 2, and 3 are all at a relatively low level (14-16 mg KOH / g), which indicates that the resins in these Examples have low acidity and may have better stability.

[0117] The acid values ​​of Comparative Examples 1 and 2 are relatively high (18-19 mg KOH / g), especially Comparative Example 2, which may mean that these resins contain more acidic impurities or incompletely reacted acidic monomers, which may affect their stability and application performance.

[0118] 2. Softening value (℃)

[0119] The softening values ​​of Examples 1, 2, and 3 are all between 85 and 88° C., indicating that these resins begin to soften at relatively high temperatures and have good heat resistance.

[0120] The softening values ​​of Comparative Examples 1 and 2 are relatively low (65-70° C.), indicating that these resins may begin to soften at relatively low temperatures and have poor heat resistance.

[0121] 3. Initial adhesion (N / 25mm)

[0122] The initial adhesion of Examples 1, 2, and 3 is between 11 and 13 N / 25 mm, indicating that these resins have good adhesion capabilities upon initial contact.

[0123] The initial adhesion of Comparative Examples 1 and 2 is relatively low (8-9 N / 25 mm), which may mean that these resins have weak adhesion ability at the initial contact.

[0124] 4. Holding strength (70℃,h)

[0125] The holding power of Examples 1, 2, and 3 is between 95 and 100 hours, indicating that these resins can still maintain good adhesion at high temperatures and have excellent holding power.

[0126] The holding force of Comparative Examples 1 and 2 is relatively low (70-85 hours), and especially at high temperatures, the holding performance is significantly inferior to that of the examples.

[0127] 5. Peel strength at room temperature 180° (N / 25mm)

[0128] The 180° peel strength at room temperature of Examples 1, 2, and 3 is between 48 and 52 N / 25 mm, indicating that these resins have high peel strength at room temperature and good adhesion strength and anti-peeling performance.

[0129] The 180° peel strength at room temperature of Comparative Examples 1 and 2 is relatively low (40-45 N / 25 mm), indicating that the adhesion strength and anti-peeling performance of these resins at room temperature are relatively poor.

[0130] 6. Comprehensive analysis

[0131] Examples 1, 2, and 3 all performed well in various performance indicators, especially in terms of acid value, softening value, initial adhesion, lasting adhesion, and 180° peel strength at room temperature, all showing performance superior to that of the comparative example.

[0132] The performance of Comparative Examples 1 and 2 is relatively poor, which is due to the lack of certain key components (such as chain transfer agents and functional fillers) in the formulation or the use of non-water-soluble monomers instead of water-soluble monomers.

[0133] The beneficial effects of the high-stability water-white tackifying resin and the preparation method thereof of the present invention are mainly reflected in the following aspects:

[0134] 1. Improve thermal stability and oxidation safety: Since the present invention adopts a fully enclosed production method, it can effectively reduce the oxidation chance of the material at high temperature. This production method significantly improves the thermal stability and oxidation safety of the water-white tackifying resin, thereby ensuring the stability and durability of the resin in long-term use or high-temperature environments.

[0135] 2. Improve color: Through a carefully designed production process, the present invention can prepare a water-white tackifying resin with a color close to color 0. This colorless or light-colored resin is not only beautiful, but also has a wider application prospect in some fields with strict requirements on color (such as high-end coatings, inks, etc.).

[0136] 3. Improve the compatibility with adhesive materials: The water-white tackifying resin prepared by the present invention has better compatibility with adhesive materials such as EVA, SIS, SBS, etc. This excellent compatibility helps to improve the adhesion and stability of the product, thereby improving the overall performance and service life of the product.

[0137] 4. Simplify the production process, reduce energy consumption and cost: The present invention reduces production links, reduces natural energy consumption and workload by optimizing the production process. This not only improves production efficiency, but also reduces production costs, making the product more competitive in the market.

[0138] 5. Improve product quality: By precisely controlling the raw material ratio and production process, the present invention can prepare a water-white tackifying resin with stable quality and excellent performance. This high-quality resin can meet various application requirements and provide users with a better use experience.

[0139] The high-stability water-white tackifying resin and the preparation method thereof of the present invention select raw materials with excellent performance and proportion, and ensure the basic performance of the resin by accurately controlling the raw material proportion.

[0140] Fully enclosed operation: During the preparation process, the present invention adopts a fully enclosed operation method, which effectively reduces the oxidation chance of the material at high temperature and improves the thermal stability and oxidation safety of the resin.

[0141] Adopt refining process: through distillation, high temperature atomization, cooling and other refining processes, impurities and heavy oil in the raw materials are removed, and the purity and stability of the resin are improved.

[0142] Using esterification reaction: On the basis of refined natural resin, catalyst and polyol are added for esterification reaction to obtain water-white tackifying resin. This step not only improves the adhesion of the resin, but also further improves the color and compatibility of the resin.

[0143] In summary, the high-stability water-white tackifying resin and the preparation method thereof of the present invention have significant beneficial effects, can meet various application requirements, and bring better use experience to users.

[0144] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited by the above embodiments. The above embodiments and descriptions are only preferred examples of the present invention and are not intended to limit the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A high stability water-white tackifying resin, characterized in that: The raw materials include the following total percentages: 32.7-58.1% of monomer A, 1.4-6.7% of monomer B, 5.2-20.5% of monomer C, 12.4-29.3% of functional monomer D and 0.1-1.3% of catalyst E, wherein: The monomer A is a water-soluble monomer comprising at least one polymerizable double bond; The monomer B includes a cross-linking agent monomer having at least two polymerizable double bonds; The monomer C comprises a modified monomer having a hydrophobic group; The functional monomer D is a monomer containing hydroxyl and carboxyl polar groups.

2. The high stability water-white tackifying resin according to claim 1, characterized in that: The invention also comprises 0.01% to 1.0% of a chain transfer agent F and 0.1% to 10% of a functional filler G.

3. The high stability water-white tackifying resin according to claim 2, characterized in that: The chain transfer agent F is selected from one or more of dodecanethiol, mercaptoethanol or β-mercaptoethanol.

4. The high stability water-white tackifying resin according to claim 2, characterized in that: The functional filler G is one or more of silicates, calcium carbonate or nano titanium dioxide.

5. The high stability water-white tackifying resin according to claim 1, characterized in that: The monomer A is selected from one of acrylic acid, methacrylic acid or acrylamide.

6. The high stability water-white tackifying resin according to claim 1, characterized in that: The monomer B is selected from ethylene glycol dimethacrylate or divinylbenzene.

7. The high stability water-white tackifying resin according to claim 1, characterized in that: The monomer C is selected from butyl methacrylate or octyl acrylate.

8. The high stability water-white tackifying resin according to claim 1, characterized in that: The functional monomer D is selected from hydroxyethyl acrylate or glycidyl methacrylate.

9. The high stability water-white tackifying resin according to claim 1, characterized in that: The catalyst E is specifically potassium persulfate or azobisisobutyronitrile.

10. A method for preparing a high-stability water-white tackifying resin as claimed in any one of claims 1 to 9, characterized in that: The specific steps include: S10 weighing materials: weighing each raw material according to weight percentage; S20 premixing: premixing the weighed monomer A, monomer B, monomer C, functional monomer D, chain transfer agent F and functional filler G uniformly; S30 Adding catalyst: slowly adding catalyst E to the mixture under stirring; S40 polymerization reaction: under nitrogen protection, heating to 60°C to 90°C to carry out free radical polymerization reaction, the reaction time is controlled at 4 to 8 hours, until the system viscosity reaches a predetermined value, the predetermined viscosity value is 500 to 5000 mPa·s; S50 post-treatment: After the reaction is completed, the temperature is lowered to room temperature, an appropriate amount of neutralizer is added to adjust the pH value to 7-9, and unreacted impurities are removed by filtration to obtain a high-stability water-white tackifying resin solution; S60 Drying and curing: remove most of the water from the above solution by spray drying or reduced pressure evaporation to obtain solid resin powder.